Solar Energy 2005
DOI: 10.1115/isec2005-76151
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production Through Two-Step Water Splitting Using YSZ (Ni,Fe) System for Solar Hydrogen Production

Abstract: The two-step water splitting with the solid solution of YSZ (Yttrium stabilized Zirconia) and Ni-ferrite (NiFe2O4) was studied for solar hydrogen production. The sample of YSZ/Ni-ferrite solid solution was prepared by calcination of the mixture of the YSZ balls and Ni-ferrite (NiFe2O4) powder. The two-step water splitting process composed of O2-releasing reaction (T = 1773K) in Ar gas flow and H2-generation reaction (T = 1473K) in Ar gas and steam flow with the YSZ/Ni-ferrite solid solution were repeated ten t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…An important consequence is that high porosity may not be needed and sintering of the porous zirconia may not be an issue. These observations appear to be in good agreement with those obtained by Ishihara et al, [16] and may be a key to the CR5 concept viability. They suggest a new type of redox material with high internal oxygen mobility for transport of oxygen to and from dispersed redox sites.…”
Section: Cr5 Developmentsupporting
confidence: 92%
See 1 more Smart Citation
“…An important consequence is that high porosity may not be needed and sintering of the porous zirconia may not be an issue. These observations appear to be in good agreement with those obtained by Ishihara et al, [16] and may be a key to the CR5 concept viability. They suggest a new type of redox material with high internal oxygen mobility for transport of oxygen to and from dispersed redox sites.…”
Section: Cr5 Developmentsupporting
confidence: 92%
“…It is slightly exothermic and is spontaneous at ambient temperature to about 1200 K. In recent years, research has focused on mixedmetal oxides called ferrites that have a spinel crystal structure involving Fe and a second metal A (where A = Mn, Mg, Co, Zn, and/or Ni) as a way to lower the temperatures required to reduce the oxide. [9][10][11][12][13] Recently, Kodama et al, [14,15] and Ishihara et al, [16] have demonstrated that dispersing the ferrite in zirconia enhances reactivity and improves reduction and hydrolysis kinetics. They have also shown that the supported materials maintain reactivity when repeatedly cycled between TR and WO reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidization of the dissolved cations has an activation energy of 53.9 kJ/mol, while the solid solution of CoOFeO has an activation energy of 141 kJ/mol. Like CoFe 2 O 4 , NiFe 2 O 4 splits water repeatedly with a high H 2 production capacity, producing roughly 179 µmol H 2 /g when deposited on YSZ and reduced at <1500°C . Similar to the cases of CoFe 2 O 4 and Fe 3 O 4 deposited on YSZ, Fe 2+ ions from the reduction of NiFe 2 O 4 dissolve into the YSZ support and NiFe 2 O 4 is stable over multiple cycles.…”
Section: Two‐step Stws Active Materialsmentioning
confidence: 90%
“…YSZFe 3 O 4 was synthesized for the cyclic two-step watersplitting reaction as a reactive ceramic, which has the stability at the temperature of the O 2 -releasing reaction and high conductivities of O 2À . The amount of H 2 evolved in the H 2 -generation reaction with YSZ-Fe 3 O 4 after the O 2 -releasing reaction at 1773 K was 1.77 cm 3 /g [13]. The temperature of the O 2 -releasing reaction with CeO 2 -Ce 2 O 3 (CeO 2 ¼ cerium dioxide) system was evaluated above 2500 K from the thermodynamic data calculated by MALT2 software [14].…”
Section: Introductionmentioning
confidence: 99%